(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2025)
This contribution provides an overview of the content of this Special Number of the Latin American Journal of Sedimentology and Basin Analysis, which explores the geological evolution of the Golfo San Jorge Basin and the challenges it faces within the current context of hydrocarbon resource depletion and global warming. The Special Number comprises eight peer-reviewed articles synthesizing current knowledge across multiple disciplines. The topics covered include: (i) magmatic evolution (Navarrete); (ii) structural geology (Allard et al.); (iii) stratigraphy and provenance (Paredes et al.; Olazábal et al.; Foix et al.); (iv) paleosol development (Lizzoli and Raigemborn); and (v) Cretaceous biostratigraphy (Pérez Loinaze; De Sosa Tomas and Vallati). These contributions present recent advances in their respective fields and highlight critical unresolved questions that must be addressed to further our understanding of the geological evolution of the Golfo San Jorge Basin.